2002
DOI: 10.1038/sj.bjp.0704631
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as a novel activator of L‐type Ca2+channels in rat tail artery smooth muscle cells

Abstract: 1 The aim of this study was to investigate the e ects of quercetin, a natural polyphenolic¯avonoid, on voltage-dependent Ca 2+ channels of smooth muscle cells freshly isolated from the rat tail artery, using either the conventional or the amphotericin B-perforated whole-cell patch-clamp method. 2 Quercetin increased L-type Ca 2+ current [I Ca(L) ] in a concentration-(pEC 50 =5.09+0.05) and voltage-dependent manner and shifted the maximum of the current-voltage relationship by 10 mV in the hyperpolarizing dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 40 publications
(36 reference statements)
5
50
0
Order By: Relevance
“…tea, red wine). 15) It has been reported that quercetin inhibited thrombocyte aggregation 16) and had an anti-hypertensive effect. 17) Interest in dietary phenolics has increased greatly recently, owing to their antioxidant properties (free radical scavenging and metal chelating) and their possible beneficial implications in human health, such as in the treatment and prevention of cancer and cardiovascular diseases.…”
mentioning
confidence: 99%
“…tea, red wine). 15) It has been reported that quercetin inhibited thrombocyte aggregation 16) and had an anti-hypertensive effect. 17) Interest in dietary phenolics has increased greatly recently, owing to their antioxidant properties (free radical scavenging and metal chelating) and their possible beneficial implications in human health, such as in the treatment and prevention of cancer and cardiovascular diseases.…”
mentioning
confidence: 99%
“…It has been reported that quercetin might be antagonizing the inward calcium membrane current, perhaps by blocking the L-type calcium membrane channels, leading to a decrease in smooth muscle contractile force (Lozoya et al, 1994). However, in another study, it has been reported that quercetin is an activator of L-type calcium channels (Saponara et al, 2002). These contradictory reports probably suggest that the spasmolytic activity of quercetin might be mediated via other mechanisms other than by antagonizing calcium membrane channels.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, these compounds have been reported to be able to protect neuronal cells in various in vitro and in vivo models through different intracellular targets [8][9][10][11][12][13]. Phenolic compounds affect the function of voltage-gated ion channels [14][15][16][17] including voltage-gated Ca 2+ channels [18]. Phenolic compounds have ability to affect agonist-induced [Ca 2+ ]i increase in neuronal cells [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%